SERVICE QUALITY AND CONSUMER PROTECTION EFFECT ON LOYALTY: TRUST AS INTERVENING VARIABLE - Saputra, Gatot Efdi; Wahyuni, Sri (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
The database of PT.PNM Aceh, especially UlaMM has shown that in the period January - PT. PNM's investigation on the relationship between customer loyalty, trust, consumer protection, and service quality produced a number of key discoveries. The findings indicate that customer trust is greatly increased by service quality, and that consumer protection is also a key factor in building customer trust. In particular, it was shown that trust significantly improved consumer loyalty. However, this study also highlights that service quality does not have a direct impact on customer loyalty, and trust is not effective as a mediating variable in this context. These findings suggest that while consumer protection greatly influences customer loyalty, the mechanisms for building loyalty in the banking sector are complex and require further exploration. This study emphasizes the importance of effective consumer protection measures and high service quality in fostering customer trust and loyalty.